Exploring Perceptions of Advantage and Attitudes Towards Redistribution in South Africa - Burns, Justine (2024)
Tackling inequalities and poverty in South Africa has proven extremely difficult and contentious. Indeed, redistribution policies are often widely criticized both by people who argue that these policies are not far‐reaching and comprehensive enough and by those who argue they are not justified, too large‐scale and/or ineffective, and should be scaled back. While public support amongst relatively advantaged South Africans is crucial for these redistribution policies to be enacted and maintained, interestingly, we know very little about how respective groups of “advantaged” South Africans from different ethnic groups view wealth transfers and other redistribution measures aimed at reducing the prevailing inequalities in South Africa. Drawing on a series of focus group discussions, we gain insights into perceptions of advantage and attitudes towards redistribution amongst groups of black and white “advantaged” South Africans respectively. We find that both black and white “advantaged” South Africans are reluctant to part with some of their wealth in the interests of greater economic equality, citing state corruption and extended network obligations as justification. In addition, there is a shared tendency to understate their economic advantage by identifying firmly as the middle class, thereby abrogating responsibility to the super‐wealthy whilst simultaneously expressing paternalistic views towards the poor.